2000
DOI: 10.1128/iai.68.8.4714-4719.2000
|View full text |Cite
|
Sign up to set email alerts
|

Bile Mediates Intestinal Pathology in Endotoxemia in Rats

Abstract: Intestinal pathology frequently accompanies experimental endotoxic shock and is mediated by proinflammatory cytokines. Our hypotheses are that hepatobiliary factors operating from the luminal side of the gut make a major contribution to this damage and that tumor necrosis factor alpha (TNF-␣) is involved in the pathology. We treated rats with lipopolysaccharide (LPS) intravenously and found that external drainage of bile totally protected the gastrointestinal tract, macroscopically and microscopically, 4 h aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 33 publications
0
26
0
1
Order By: Relevance
“…It is known that accumulation of BA in the intestine can result in damage to the intestinal epithelium (28). Our previously published data strongly suggest that accumulation of BA in the ileum during experimental NEC is a critical component of disease development, a novel concept in experimental NEC pathogenesis (17).…”
Section: Discussionmentioning
confidence: 98%
“…It is known that accumulation of BA in the intestine can result in damage to the intestinal epithelium (28). Our previously published data strongly suggest that accumulation of BA in the ileum during experimental NEC is a critical component of disease development, a novel concept in experimental NEC pathogenesis (17).…”
Section: Discussionmentioning
confidence: 98%
“…Bile duct cannulation was carried out as described previously (Jackson et al, 2000) under anesthesia (a combination of 90 mg/kg ketamine and 10 mg/kg xylazine). A dose of 50 mg/kg chrysin (dissolved in dimethyl sulfoxide at a concentration of 20 mg/ml) or vehicle (dimethyl sulfoxide) was first given to rats via i.p.…”
Section: Methodsmentioning
confidence: 99%
“…This indicates that Kupffer cells, instead of hepatocytes, play an important role in triggering inflammation. LPS challenge not only decreases the rate of bile flow (2, 10), which is important to maintain gut homeostasis, but also stimulates macrophages to release TNF-␣ into the bile (12). It has been shown that TNF-␣ concentration in the bile of LPS-challenged animals is 30 times higher than that in the serum (12).…”
mentioning
confidence: 99%